A handbook on Isaiah - Waard, Jan de (Textual criticism and the translator ;, 1997)
In this volume, the first of a projected series on the Hebrew Bible, de Waard aims to give translators better insight into the viewpoint of the textual critic to help them find a good base for translation. Though of primary interest for translators, students and scholars will also be pleased to find that de Waard summarizes the arguments and ratings of the Hebrew Old Testament Text Project.Because the final report of the HOTTP was published in French and was the work of textual critics rather than translation specialists, its valuable contribution was found to have practical limitations. DeWaard's work is also valuable because it examines three major Jewish versions in addition to the Christian versions selected by the Project for study.Future volumes are planned to cover other portions of the Hebrew Bible/Old Testament.